Rwa Bhineda concept and weighted product method in the Alkin-Provus evaluation model modified design - Sugandini, Wayan; Suyasa, P. Wayan Arta; Divayana, Dewa Gede Hendra; Ariawan, I Putu Wisna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The combination of the Alkin and Provus evaluation models was carried out to optimize the functionality of the evaluation components owned by each evaluation model. Although the combination of the two models was perfect, there were still obstacles in its implementation. The obstacle was the difficulty in determining the priority aspects in the evaluation components that trigger the effectiveness of a program/object being evaluated. Therefore, it is urgent to conduct research that shows innovations in the form of modifications made to the two evaluation models by utilizing the Rwa Bhineda concept and the Weighted Product method. The Rwa Bhineda concept is used to determine the accuracy of the integration of the evaluation aspects owned by each evaluation component of the Provus and Alkin models. The Weighted Product method is used to obtain calculation results in determining the priority aspects that trigger the effectiveness of a program. The purpose of this study was to show the quality of the modified design of the Alkin-Provus evaluation model that utilizes the Rwa Bhineda concept and the Weighted Product method. This study used a development approach. The development model, as proposed by Borg & Gall, encompasses three stages: design creation, initial design trials, and revision of initial design trials. The subjects involved in the initial design trial were 50 respondents. The selection of subjects used a purposive sampling technique. The initial trial tool was a questionnaire consisting of 15 questions related to the design. The data analysis technique for the trial results was quantitative descriptive. This technique involves comparing the percentage of design quality with quality standards that refer to the five-scale categorization. The results of this study indicate that the modified design of the Alkin-Provus evaluation model, which utilizes the Rwa Bhineda concept and the weighted product method, falls within the good quality category. The impact of the results of this study is that evaluators and observers in the field of education gain knowledge about the existence of the concept of Balinese local wisdom (namely Rwa Bhineda) and the decision support system method (namely Weighted Product) that can be used to optimize the functionality of the Provus and Alkin evaluation components and determine the priority aspects that trigger the effectiveness of a program/object being evaluated.